2022
DOI: 10.3389/fmicb.2022.950913
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic Effects of Fermented Rice on Human Health and Wellness: A Natural Beverage That Boosts Immunity

Abstract: Fermented foods have been an important component of the human diet from the time immemorial. It contains a high amount of probiotics that have been associated to a wide range of health benefits, including improved digestion and immunity. This review focuses on the indigenously prepared prebiotic- and probiotic-containing functional fermented rice (named Xaj-pani) by the Ahom Community from Assam, in Northeast India, including all the beneficial and potential effects on human health. Literature was searched fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…Fewer studies have investigated the potential probiotic strains from rice water fermented for 6 to 7 h. Several studies have claimed microbial diversity in different ethnic rice-based fermented foods but not in rice water which is widely drunk across rice cultivating regions worldwide, for its potential health benefits ( 46 ). Rice water with proper supplementation is also recognized as equivalent or better than WHO-formulated glucose-based ORS in many respects, as described by ( 12 , 47 ). Very often, this boiled rice water gets fermented while stored.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have investigated the potential probiotic strains from rice water fermented for 6 to 7 h. Several studies have claimed microbial diversity in different ethnic rice-based fermented foods but not in rice water which is widely drunk across rice cultivating regions worldwide, for its potential health benefits ( 46 ). Rice water with proper supplementation is also recognized as equivalent or better than WHO-formulated glucose-based ORS in many respects, as described by ( 12 , 47 ). Very often, this boiled rice water gets fermented while stored.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are defined as microbial organisms with a beneficial role in the host’s health and homeostasis, which help to preserve digestive, metabolic, immune, and neuroendocrine functions [ 202 ]. Naturally probiotic bacteria can be found in fermented food [ 203 , 204 ]. Experimental results revealed that the administration of probiotics alone or in combination with prebiotics (fructooligosaccharides or galactooligosaccharides) improved the gastrointestinal barrier [ 205 , 206 ], which is the first line of “defence” from harmful factors occurring in food, and the microbiome.…”
Section: Nutritional Intervention As a Promising Solution To Prevent ...mentioning
confidence: 99%
“…They are often known as "beneficial" bacteria since they assist in maintaining a harmonious microbial environment within the digestive system [11]. Probiotic microbiome is commonly utilized in dietary supplements and also found naturally as live microflora in a variety of fermented food products that people consume [12]. The ways in which probiotics positively impact on human health involves in multiple molecular mechanisms including enhancing regulating the response of immune, the strength and function of the intestinal barrier, and counteracting infectious agent by producing antimicrobial substances or competing for binding sites against mucosal surface [13].…”
Section: Introductionmentioning
confidence: 99%